Konstruksi Narasi Perempuan Muslimah pada Tren Fashion Syariah di Gontornews.com dan Chanelmuslim.com - Eka Candelia, Dera; Aditya Maulana, Lukman (Journal of Islamic Communication Studies, 2025)
The trend of Sharia fashion is growing in Indonesia alongside increasing public awareness of the halal lifestyle. This has attracted public attention, leading the media to produce extensive content and news related to Sharia fashion trends that portray Muslim women. The media plays a crucial role in shaping public perceptions of Sharia fashion, particularly in constructing the identity of Muslim women. This study aims to analyze how Gontornews.com and Chanelmuslim.com frame the narrative of Muslim women in the Sharia fashion trend. Using a constructivist approach and Robert N. Entman’s framing analysis, this research explores four key framing elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. Data were collected from news articles published on both portals between August 2, 2024, and January 22, 2025. The findings reveal that Gontornews.com views the hijrah trend as a driving force in the Muslim fashion industry, while Chanelmuslim.com highlights the challenges Muslim women face in dressing modestly yet stylishly. Gontornews.com emphasizes social and cultural influences on fashion preferences, whereas Chanelmuslim.com focuses more on individual awareness. Both agree that Muslim fashion should reflect Islamic values; however, Gontornews.com underscores religious compliance, while Chanelmuslim.com highlights the balance between trends and Muslim identity. In terms of recommendations, Gontornews.com encourages innovation within the industry, whereas Chanelmuslim.com urges Muslim women to remain fashionable without blindly following trends. Both media outlets construct narratives that reinforce the identity of Muslim women as key players in the Sharia fashion industry and agents of social change. These findings affirm that the media not only disseminates information but also constructs social reality, shaping public perceptions of Sharia fashion and the identity of Muslim women in Indonesia.